Structure and Reaction Mechanism of Pyrrolysine Synthase (PylD)1. Issue 27 (29th May 2013) - Quitterer, Felix; Beck, Philipp; Bacher, Adelbert; Groll, Michael
<x xml:space="preserve">Abstract</x> The final step in the biosynthesis of the 22nd genetically encoded amino acid, pyrrolysine, is catalyzed by PylD, a structurally and mechanistically unique dehydrogenase. This catalyzed reaction includes an induced‐fit mechanism achieved by major structural rearrangements of the N‐terminal helix upon substrate binding. Different steps of the reaction trajectory are visualized by complex structures of PylD with substrate and product.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>